IRBESARTAN IN THE CLINICAL PRACTICE - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии, 2015)
Only few hypertensive patients are treated effectively despite of the variety of antihypertensive drugs. There is a linear relationship between blood pressure levels and the risk of complications (myocardial infarction, stroke, chronic heart and renal failure). Angiotensin receptor blockers are the first-line drugs for initial therapy of uncomplicated hypertension. Irbesartan is one of the most studied angiotensin receptor blockers. Data supporting the high antihypertensive and nephroprotection efficacy of irbesartan as well as its ability to reduce cardiovascular risk in hypertensive patients are presented.